Rural Electrification in Tunisia : National Commitment, Efficient Implementation and Sound Finances - Cecelski, Elizabeth (World Bank, Washington, DC, 2014)
Tunisia's achievement of 100 percent urban and 88 percent rural electrification is remarkable, all the more so because the country's definition of rural electrification is restricted to connections made outside incorporated areas. Compared to rural populations in other developing countries with high rates of electrification, Tunisia's rural population-although only 35 percent of the total population-is highly dispersed and isolated, with long distances between small groups of often scattered houses. This characteristic, combined with the Government's social commitment to connecting all households, has highly influenced program costs and choice of institutional set-up, distribution system, and technology. This paper reports on the major factors contributing to Tunisia's successful rural electrification program, primarily: 1) the national commitment to rural electrification as part of a broader, integrated rural development program emphasizing social equity; 2) an effective institutional structure and coordination of project planning and selection; 3) the utility's sound management and continuing process of technical innovation; 4) the robust financial arrangements; and 5) the complementary strategy of using photovoltaic cells to serve isolated users.